Preclinical Development of a Genetically Engineered Albumin‐Binding Nanoparticle of Paclitaxel - Soumen Saha; Samagya Banskota; Parisa Yousefpour; Jeffrey L. Schaal; Nikita Zakharov; Jianqiao Liu; Michael Dzuricky; Ziwei He; Stefan Roberts; Xinghai Li; Ashutosh Chilkoti (Small Science)
Nab‐paclitaxel (Abraxane), an albumin‐bound solvent‐free paclitaxel (PTX) formulation that takes advantage of the endogenous albumin transport pathway, is the current gold standard for treatment of solid tumors with PTX. However, nab‐paclitaxel has several limitations, including complex manufacturing, immunogenicity, slow drug‐release, and a narrow therapeutic window. Nevertheless, no other PTX formulation has gained the Food and Drug Administration approval since Abraxane's 18‐year reign. Addressing these concerns, herein, a PTX‐loaded nanoparticle of a recombinant polypeptide that—like nab‐paclitaxel—capitalizes on the long in vivo half‐life of albumin is reported. This genetically engineered nanoparticle packages PTX in the core of the nanoparticle and displays an albumin‐binding domain on the exterior of the nanoparticle. Upon in vivo administration, the drug‐loaded nanoparticle binds albumin with nanomolar affinity, and acquires an albumin‐corona, which eliminates the need to use exogenous albumin. The nanoparticles can be stored at subzero temperature as lyophilized powder without any cryoprotectants for upto a year and can be reconstituted on‐demand in aqueous buffer at high concentration, thus greatly simplifying formulation processes. These albumin‐binding nanoparticles improve the therapeutic window by at least twofold compared to nonalbumin‐binding counterpart and outperform nab‐paclitaxel in multiple murine tumor models, results that have been independently replicated by a contract research organization.